Beyond Physical Boundaries: Assessing Managers’ Intentions to Adopt Virtual Reality Technology in Wine Tourism - Sousa,Nuno (2025)
Abstract Virtual Reality (VR) has been recognised as a promising technology for enhancing the tourist experience. However, little is known about the intention of tourism business managers to adopt VR for leisure purposes. In this context, this study aims to explore this intention by interviewing managers in the sector. This process allowed us to examine their perceptions regarding the use of this technology in their business models. The results revealed that the perceived usefulness of VR is a key factor in its adoption. In addition, managers recognise the value of VR as a complement to the tourist visit, and their intention to adopt it increases when a positive return on investment is anticipated. This approach offers a unique perspective on the main factors influencing technology adoption in this context, broadens the understanding of VR applications in wine tourism, and highlights its potential to transform the visitor experience and drive growth in the sector through innovative business models.